2006
DOI: 10.1002/gps.1690
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary metabolomic analysis of older adults with and without depression

Abstract: These observations suggest that the depressed state may be associated with alterations in the metabolism of lipids and neurotransmitters, and that treatment with antidepressants adjusts some of the aberrant pathways in disease so that the patients in remission have a metabolic profile more similar to controls than to the depressed population. These results will need to be examined and validated in larger longitudinal cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 23 publications
1
97
0
Order By: Relevance
“…Our search identified 45 studies: 26 studies for the comparison of patients with current MDE versus healthy controls, [8][9][10][11][12][13][14][15][16][17][18]30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] 12 studies for the comparison of patients with current MDE before treatment versus after treatment, 12,20,23,25,26,28,36,43,[47][48][49][50] and 11 for the comparison of euthymic patients and controls. 18,[21][22][23]27,29,38,[51][52][53][54] Figure 1 depicts the study selection proce...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search identified 45 studies: 26 studies for the comparison of patients with current MDE versus healthy controls, [8][9][10][11][12][13][14][15][16][17][18]30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] 12 studies for the comparison of patients with current MDE before treatment versus after treatment, 12,20,23,25,26,28,36,43,[47][48][49][50] and 11 for the comparison of euthymic patients and controls. 18,[21][22][23]27,29,38,[51][52][53][54] Figure 1 depicts the study selection proce...…”
Section: Resultsmentioning
confidence: 99%
“…18,[21][22][23]27,29,38,[51][52][53][54] Figure 1 depicts the study selection process, and the included plasma, CSF and MRS studies are described in Table 1, Table 2 and Table 3, respectively. We excluded 3 studies assessing plasma GABA levels 44,48,55 and 5 studies 34,45-47,52 assessing CSF GABA levels from our analyses because clinical samples included patients with unipolar and bipolar depression, and no independent analysis was reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on prefrontal cortex post mortem samples from bipolar patients reports specific metabolic changes associated with notable increases in glutamate, myo-inositol and creatine (Lan et al, 2009). Importantly, treatment of rats with the mood-stabilizing agent lithium decreases the glutamine/glutamate ratio, myo-inositol and creatine levels in the were identified in serum samples from bipolar patients (Sussulini et al 2009) and MDD patients (Paige et al 2007). These studies revealed specific metabolic signatures involving variations in lipids, neurotransmitters and energy-related metabolites (lactate, acetate for BD and 3-hydroxybutanoic acid for MDD).…”
Section: Psychiatric Conditionsmentioning
confidence: 99%
“…Metabolic differences have been found in neurological and psychological disorders, such as Parkinson's disease, depression and schizophrenia, using a focused metabolomics approach [30][31][32] , indicating that it could also be a promising tool to assist in the discovery of suitable biomarkers and in revealing the detailed pathogenesis of AD. an aggressive early-onset model of amyloidosis [33] .…”
Section: Metabolomics and Admentioning
confidence: 99%